Agroecosystem diversification with legumes or non-legumes improves differently soil fertility according to soil type - Sauvadet, M.; Trap, J.; Damour, G.; Plassard, C.; Meersche, K. van den; Achard, R.; Allinne, C.; Autfray, P.; Bertrand, I.; Blanchart, E.; Deberdt, P.; Enock, S.; et al. (Elsevier, 2021)
Plant diversification through crop rotation or agroforestry is a promising way to improve sustainability of agroecosystems. Nonetheless, criteria to select the most suitable plant communities for agroecosystems diversification facing contrasting environmental constraints need to be refined. Here, we compared the impacts of 24 different plant communities on soil fertility across six tropical agroecosystems: either on highly weathered Ferralsols, with strong P limitation, or on partially weathered soils derived from volcanic material, with major N limitation. In each agroecosystem, we tested several plant communities for diversification, as compared to a matching low diversity management for their cropping system. Plant residue restitution, N, P and lignin contents were measured for each plant community. In parallel, the soil under each community was analyzed for organic C and N, inorganic N, Olsen P, soil pH and nematode community composition. Soil potential fertility was assessed with plant bioassays under greenhouse controlled climatic conditions.